2006
DOI: 10.1177/107110070602701011
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Primary Stiffness of Tibiotalar Arthrodesis with an Intramedullary Compression Nail and Four Other Fixation Devices

Abstract: Intramedullary compression nailing offers stable tibiotalar arthrodesis fixation with a large bony contact area and may enhance the likelihood of successful tibiotalar arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…19,27,32,35,37 Biomechanical studies have improved our understanding of the best fixation techniques to reduce the risk of nonunion. 5,6,8,14,17,24,25,30,33,34 Failure of revision procedures has also been reported with relatively high rates and occasionally below-knee amputation is the final salvage operation. 1,11,21,28,31,38 Even when arthrodesis is successful, postoperative complications are common and patients occasionally report high levels of pain postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…19,27,32,35,37 Biomechanical studies have improved our understanding of the best fixation techniques to reduce the risk of nonunion. 5,6,8,14,17,24,25,30,33,34 Failure of revision procedures has also been reported with relatively high rates and occasionally below-knee amputation is the final salvage operation. 1,11,21,28,31,38 Even when arthrodesis is successful, postoperative complications are common and patients occasionally report high levels of pain postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…Fusion has been attempted with screws, pins, plates, nails, casting with bone grafting, external fixation and combinations of these devices [16][17][18][19], and previous articles have detailed their development [1,3,15]. In 1951, compression arthrodesis was introduced using external fixation [20].…”
mentioning
confidence: 99%
“…Many operative techniques involving screws, plates, pins, external fixators, and intramedullary nails (IMNs) have been used to achieve TTC arthrodesis. 1,6 Compared with other fixation methods, IMNs have been shown to have higher bending stiffness, increased rotational stability, and dynamic compression capability. 7 Berson et al 7 demonstrated that more compression was achieved and maintained when an ankle arthrodesis nail-mounted compression device was compared with external fixation.…”
mentioning
confidence: 99%